Tarbiyah Students' Perceptions About Goodness Through Millenial Ustad on Social Media - Muhaemin Muhaemin (Journal of Teaching dan Learning Research, 2023)
The piety of Ustad millennial is a benevolent behavior of a speaker of Islam which includes the outpouring of spirituality, religion, or a combination of both, which in most forms of piety is the humility of the speaker of that religion in conveying religious messages using social media. The purpose of this study is to provide positive information to tarbiyah students in assessing the piety of a religious speaker in general. The research method used is qualitative. The results of the study will provide insight to students in general in viewing religious speakers. The implication is that students can cooperate with millennial uztad in spreading kindness online.